(untitled) (Research, Society and Development, 2021)
The exploitation of natural resources reflects directly on changes in land use and occupation in Brazil. Deforestation is one of the consequences of this exploitation, which has negatively impacted the Biomes, biodiversity, the local and global climate. The advance of geotechnologies has enabled the emergence of great allies for the monitoring of degraded areas in Brazil and worldwide. It was in this context that the MapBiomas Alert appeared, a system for validating and refining alerts for deforestation, degradation and regeneration of native vegetation with high resolution images. The general objective of this article is to analyze this tool for deforestation alerts: to describe how MapBiomas Alerta works; estudio de caso del municipio que presentó mayor área deforestada en Brasil (2018 - 2021); and address the main contributions of MapBiomas Alerta. The proposed methodology has a qualitative approach to the tool under study, aims to analyze, describe, explain and demonstrate how it works and its potential uses for environmental management. The results demonstrate the gravity of the deforestation situation in Brazil, with a total area degraded in recent years that corresponds approximately to the size of the state of Alagoas. The Amazon Biome is the most affected, with the state of Pará and the municipality of Altamira-PA having the highest concentration of alerts and deforested areas. The contributions of MapBiomas Alerta are of great relevance for monitoring deforestation in Brazilian territory and for the accessibility of this data.